Meningkatkan motivasi dan efikasi diri penderita diabetes tipe 2 dalam pencegahan kaki diabetik menggunakan dukungan kelompok - Suyanto Suyanto; Dwi Sulistyowati (Holistik Jurnal Kesehatan, 2020)
Improving motivation and self-efication of type 2 diabetics in prevention of diabetic foot ulcers and infections using group supportBackground: Management of DM (Diabetics) patients according to expectations requires a variety of support, one of them is group support such as the Persadia Club as an organization that helps people with diabetes to manage disease conditions become more controlled. Through group support, motivation and self-efficacy which are important factors in diabetes care behavior will increase. Thus the main action in the prevention of diabetic foot in the form of routine foot care will be carried out by the person with diabetes optimally.Purpose: To determine the effect of group support on motivation and self-efficacy of type 2 diabetics in prevention of diabetic foot ulcers and infectionsMethods: The study design was a quasi-experimental one pre group test one group method to see if there were differences in motivation and self-efficacy in diabetic foot care before and after group support. The study was conducted in May to August 2019 at the Surakarta City Persada Club as a population and a sample of 135 respondentResults: Research shows that there are differences in the self-efficacy of people with diabetes before and after getting group support with p value = 0,000. Thus the hypothesis that the influence of group support on self-efficacy is accepted. Furthermore, the results obtained that there are differences in motivation to take preventive measures for diabetes feet between before and after group support is given with a p value = 0,000. This means that the hypothesis that there is an influence of group support on motivation for diabetic foot prevention.Conclusion: As a suggestion, it is expected that people with diabetes through the Persadia club will always be supported so that their motivation and efficacy is high so that the diabetic foot care measures will be optimally carried out. Keywords: Motivation; Self-Efication; Type 2 Diabetics; Prevention; Diabetic Foot Ulcers and Infections; Group SupportPendahuluan: Pengelolaan pasien DM (Diabetisi) yang sesuai harapan memerlukan berbagai dukungan salah satu diantaranya yaitu dukungan kelompok seperti Club persadia sebagai organisasi yang membantu para diabetisi untuk mengelola kondisi penyakit  menjadi lebih terkontrol. Melalui dukungan kelompok  maka motivasi dan efikasi diri yang merupakan faktor penting dalam perilaku perawatan diabetes akan meningkat. Dengan demikian tindakan utama dalam  pencegahan kaki diabetik berupa tindakan perawatan kaki secara rutin akan dilakukan para diabetisi dengan optimal.Tujuan: Untuk mengetahui pengaruh dukungan kelompok terhadap motivasi dan efikasi diri  penderita diabetes tipe 2 dalam pencegahan kaki diabetikMetode : Rancangan penelitian berupa kuasi eksperimen dengan metode pre post test one group untuk melihat apakah terdapat perbedaan  motivasi dan  efikasi diri dalam tindakan perawatan kaki diabetik sebelum dan sesudah mendapat dukungan kelompok.  Penelitian dilakukan pada bulan Mei hingga Agustus 2019 pada Club Persadia Kota Surakarta  sebagai populasi dan diambil sampel sebanyak 135 respondenHasil: Penelitian menunjukkan bahwa terdapat perbedaan efikasi diri para diabetisi sebelum dan sesudah mendapt dukungan kelompok dengan p value = 0,000,  Dengan demikian hipotesis terdapat pengaruh dukungan kelompok terhadap efikasi diri diterima. Selanjutnya diperoleh hasil bahwa terdapat perbedaan motivasi melakukan tindakan perawatan pencegahan kaki diabetes antara sebelum dan sesudah diberikan dukungan kelompok dengan nilai p value= 0,000.  Hal ini berarti hipotesis terdapat pengaruh dukungan kelompok terhadap motivasi tindakan perawatan pencegahan kaki diabetis.Simpulan: Sebagai saran diharapkan para diabetisi melalui club Persadia selalu diberi dukungan agar motivasi dan efikasi dirinya tinggi sehingga tindakan perawatan kaki diabetik akan optimal dilakukan